Design and Psychometrics of the Sexual-Reproductive Needs and Concerns Scale of Iranian Never-Married Women Over 35 - Shakiba Pourasad Shahrak; Serge Brand; Ziba Taghizadeh; Abbas Ebadi (Tehran University of Medical Sciences, 2024)
Objective: The purpose of the present study was to design the Farsi Scale of Sexual-Reproductive Needs and Concerns of never-married women over 35 and to assess its psychometric properties. Materials and methods: This mixed method research had two phases. The first phase was qualitative (Conventional Content Analysis). We interviewed never-married Iranian women over 35; from their responses, we extracted specific statements which to be used as questionnaire items. To validate the questionnaire psychometrically, we tested its validity (face, content, and structure) and reliability (internal consistency and stability). For qualitative face validity, 15 never-married women and 5 experts commented on the style of sentences. For quantitative face validity, we used the impact score. For qualitative content validity, 15 experts commented on the items based on their appropriateness, and for quantitative content validity, we performed the Content Validity Ratio and Content Validity Index. Exploratory Factor Analysis was used to Construct Validity. To evaluate structural validity, a cross-sectional sample of 240 never-married women over the age of 35 completed the questionnaire. Cronbach's Alpha was used for internal consistency. In addition, the test-retest method and Intraclass Correlation Coefficient were used to ensure stability. Results: The Sexual-Reproductive Needs and Concerns Scale of Iranian Never-Married Women over 35 was developed with 15 items and three dimensions (Emotional burden; Sexual needs; Stigma). Cronbach's alpha for the instrument was 0.81 and the Intraclass Correlation Coefficient was 0.98. Conclusion: The results of the study showed that the developed scale has acceptable validity and reliability, and thus can be used to assess the sexual-reproductive needs and concerns of never-married Iranian women of 35 and over.